Association of sirtuin-1 and vascular endothelial growth factor expression with tumor progression and poor prognosis in liposarcoma. Issue 6 (June 2020) - Wu, Hongzeng; Zhang, Qianqian; Zhao, Yi; Xu, Fengzhou; Zhang, Jinming; He, Hongyan; Wang, Xu; Feng, Helin
Objectives: A relationship exists between sirtuin-1 expression and growth and survival of malignant tumors. This study aimed to investigate the prognostic value of sirtuin-1 and vascular endothelial growth factor (VEGF) expression in patients with liposarcoma by examining associations between their expression levels and clinical outcomes. Methods: Clinical and histopathological characteristics and follow-up and survival information were retrospectively reviewed for 42 liposarcoma cases. Sirtuin-1 and VEGF protein expression levels were evaluated by immunohistochemistry and their associations with clinical parameters were analyzed using the Spearman-rho test. Univariate and multivariate Cox regression analyses were performed to identify potential prognostic factors. Kaplan–Meier analysis was performed to analyze overall survival. Results: Sirtuin-1 and VEGF protein expression levels were significantly associated with histological grade, metastasis, and American Joint Committee on Cancer stage. A significant positive correlation was observed between sirtuin-1 and VEGF expression levels (R = 0.677). In univariate analysis, sirtuin-1 and VEGF expression were correlated with shorter overall survival, but the association was significant only for sirtuin-1 (hazard ratio = 3.752, 95% confidence interval 1.553–9.062) in multivariate analysis. Conclusion: Sirtuin-1 and VEGF expression levels are significantly correlated with progression of liposarcoma, and sirtuin-1 expression significantly predicts a poor prognosis in patients with liposarcoma.